Hash Performance Optimization with ParallelHash for Hyperledger Fabric Acceleration - Crozariolo, João Pedro Correa; Giron, Alexandre Augusto (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.11816, 2025)
Hyperledger Fabric’s integrity relies on hash functions, but sequential standards like SHA-2 create bottlenecks in large-data operations like ledger snapshot verification. This work investigates replacing SHA-2 with the ParallelHash family by implementing and benchmarking ParallelHash128/256 in Go, demonstrating significant throughput gains. The practical integration challenges are also analyzed, identifying hardcoded limitations in Fabric’s source code that hinder crypto agility. The findings offer a roadmap for enhancing Fabric’s performance using modern cryptographic primitives.